Mobile-Based Training and Monitoring Information System for LPK Multi Karya - Raihan, Maulana; Fachrie, Muhammad (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
LPK Multi Karya faces challenges in efficiently managing training due to the vast area of Central Kalimantan, which makes it difficult for trainers to reach participants in remote areas. This results in suboptimal training services and monitoring of participant activities. This study aims to develop a Mobile-Based Information and Monitoring System to improve data management, activity monitoring, and operational efficiency of the institution. The system development method includes needs analysis, design using the Prototype method, implementation, and evaluation. System testing results show that the system functions well and enhances the efficiency of schedule management, access to training information, and real-time monitoring of participant activities. This research contributes to the digitalization of the training sector, supports the improvement of service quality, and serves as a reference for other training institutions.Keyword: Information systems; Training; Learning; Monitoring; ServicesÂ AbstrakLPK Multi Karya menghadapi tantangan dalam efisiensi pengelolaan pelatihan akibat luasnya wilayah Kalimantan Tengah, yang menyulitkan pelatih menjangkau peserta di daerah terpencil. Dampaknya adalah kurang optimalnya layanan pelatihan dan monitoring kegiatan peserta. Penelitian ini bertujuan mengembangkan Sistem Informasi dan Monitoring berbasis mobile untuk meningkatkan pengelolaan data, pemantauan kegiatan, dan efisiensi operasional lembaga. Metode pengembangan sistem meliputi analisis kebutuhan, perancangan menggunakan metode Prototype, implementasi, dan evaluasi. Hasil pengujian sistem menunjukkan bahwa sistem berjalan dengan baik dan dapat meningkatkan efisiensi pengelolaan jadwal, akses informasi pelatihan, dan monitoring kegiatan peserta secara real-time. Penelitian ini berkontribusi pada digitalisasi sektor pelatihan kerja, mendukung peningkatan kualitas layanan, dan menjadi acuan bagi lembaga pelatihan lainnyaÂ